Numerical Solution of Polynomial Equations using Ostrowski Homotopy Continuation Method (MATEMATIKA, 2014)
It is known that homotopy continuation methods (HCM) used in con- junction with a classical numerical method to compute roots of nonlinear algebraic equations can improve the performance of the classical numerical method. In this pa- per, we develop an Ostrowski-HCM method and apply it to solve several polynomial equations. The results obtained indicate that Ostrowski-HCM performs better than Ostrowski’s method. Keywords : Numerical method; Polynomial equations; Ostrowski’s method; Homo- topy continuation method. 2010 Mathematics Subject Classiﬁcation 65H05; 65H10; 65H20.